Beetles (Coleoptera) of Peru, a survey of the families: Sphindidae Jacquelin du Val, 1860, Corylophidae LeConte, 1852, and Latridiidae Erichson, 1842 - McHugh, Joseph V. (2022)
Three beetle families, Sphindidae Jacquelin du Val, Corylophidae LeConte and Latridiidae Erichson, are documented as part of the “Beetles of Peru” project. The checklists are based on fieldwork in Peru, museum specimens, and published literature. Three sphindid genera are indicated as new country records.